Rate of nematode infestation of clean banana planting material (Musa spp. AAA) in Uganda - Gold, C.; Goossens, B.; Karamura, E.B.; Elsen, A.; Waele, D. de; Speijer, P. (2000)
Highland cooking bananas (Musa spp. AAA) are a major staple in Eastern Africa. However, plant parasitic nematodes comprise a primary production constraint. Planting of infested material is the principle means of dispersal for these nematodes, as well as banana weevil and fusarium wilt. Nematode infestation of banana planting material can be highly reduced, using hot-water treatment, and through tissue culture techniques they can be eliminated. The benefits of nematode-free material for production, however, depend on the rate of (re)-infestation. Therefore, experiments were set up on-station (Sendusu) and in collaboration with farmers at Ikulwe and Ryeru. On station density of Radopholus similis and Helicotylenchus multicinctus in hot water treated planting material remained significantly lower (P < 0.001) than in material infested at planting over a period of 36 months after planting, irrespective of the type of management. In the farmers' fields at Ikulwe R. similis and H. multicinctus remained significantly lower (P < 0.05) in the hot water treated than in the untreated farmers' material over a period of 30 months. At this site clean material was planted adjacent to the existing banana stand. However, at Ryeru, the material was planted into existing plots and the hot-water treated material was rapidly infested. Due to the relative slow rate of nematode re-infestation, clean material, planted adjacent to the existing banana stand, may allow a management option whereby farmers select material from this clean source to further expand their plantation.